Pemanfaatan Audio Visual dalam Pembelajaran Sejarah Kebudayaan Islam Kelas 4 Madrasah Ibtidaiyah Muhammadiyah Haurgeulis - Siti Jubaedah; Abdur Rahim (Melati Institute, 2022)
Islamic Culture History is an event that occurred in the past since Islam existed as a result of human cultivation since the religion taught by Allah SWT to humanity through the Prophet Muhammad SAW, Islamic knowledge in Madrasah Ibtidaiyah (MI) aims to provide knowledge about the history of religion Islam and Islamic culture at the time of the Prophet Muhammad SAW and Khulafaurrasyidin to students so that they have an objective and systematic concept in the historical perspective, taking ibrah about the meaning contained in history, especially in subjects of Islamic Cultural History (SKI) by utilizing audio-visual media in its learning. The method used in this study is a qualitative method with a descriptive approach. The subjects in this study were students of grade IV Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis. The technique used is observation during the teaching and the learning process, structured and unstructured interviews. So, the results of the above study can be concluded that the use of audio-visual media in madrasah ibtidaiyah can improve student learning outcomes and achievements expected especially in the subjects of Islamic Cultural History (SKI).